2020
DOI: 10.3846/transport.2020.12869
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Airport Efficiency in East China Using a Three-Stage Data Envelopment Analysis

Abstract: This paper evaluates the Technical Efficiencies (TEs) of a group of airports in East China by applying a three-stage Data Envelopment Analysis (DEA) method. The merit of this method allows us to consider the impact of the environmental factors on measuring airport efficiencies. Three variables, i.e. per capita Gross Domestic Product (GDP), the proportion of the tertiary industry, and the number of tourists, are used to represent the environmental factors. The results show that the environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In a broader sense, the listed similar units from each sample are additionally similar to the units of the other samples as components of the transportation system, which according to Sinha (2007) constitute: 1. Infrastructure: distribution centers (Andrejić, 2013), airports (Zeng et al, 2020), (Shang et al, 2022), roads (Fancello et al, 2020) and container terminals (Bernal et al, 2022); 2. Vehicles: electric vehicles and internal combustion engine vehicles (Lee & Kim, 2023); 3.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a broader sense, the listed similar units from each sample are additionally similar to the units of the other samples as components of the transportation system, which according to Sinha (2007) constitute: 1. Infrastructure: distribution centers (Andrejić, 2013), airports (Zeng et al, 2020), (Shang et al, 2022), roads (Fancello et al, 2020) and container terminals (Bernal et al, 2022); 2. Vehicles: electric vehicles and internal combustion engine vehicles (Lee & Kim, 2023); 3.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conclusively, an example was, provided in this study to demonstrate the feasibility and validity of the suggested method. Zeng, et al [2020] this research employed a three-stage Data Envelopment Analysis (DEA) method to assess the Technical Efficiencies (TEs) of collection of airports in East China. The benefit of this strategy is that it allows us to analyze the impact of environmental conditions on airport efficiencies.…”
Section: Journal Articles and Conference Papersmentioning
confidence: 99%